An efficient technique for solving the two-dimensional heat equation (Statistics, Optimization & Information Computing, 2025)
In this paper, we apply the semi analytic iterative method to the solution of the two-dimensional heat equation. By means of some numerical examples we show that this method is efficient and accurate in producing exact to near-exact solutions. Even where the exact solution is unknown, we were able to obtain it through the fast convergence of the method.